Fuel atomization in gas turbines: a review of novel technology - Eid Thafnan Alajmi, Amer Eid Salem; Adam, Nor Mariah; Hairuddin, Abdul Aziz; Abdullah, Luqman Chuah (John Wiley & Sons, 2019)
The atomization of fuel is crucial in the combustion and emission of a gas turbine, and the fuel atomization is continuous without any cycles or strokes. However, to achieve a desired amount of combustion during this continuous process, fuel must be added and mixed with the high-pressure air exiting the compressor in proper proportions. To make the engine as small and lightweight as possible is a constraint and requires the fuel injection, mixing, and combustion to occur within the smallest volume possible. In most cases, this is inefficient and less practicable. A major drawback is the requirement of high injection pressure with relatively small increase in flow rate. In recent years, research was conducted to improve fuel atomization in a gas turbine by using different novel approaches that were simpler, more adaptable, and efficient to enhance the atomization. However, most of these studies were in isolation without any comprehensive literature on recent trends. Therefore, this review attempts to give an insight on recent development of fuel atomization in a gas turbine. Particular emphasis was given to air-, plasma-, ultrasound-, and supercritical fluid–assisted atomization techniques.